(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Since declaration of independence in Kazakhstan culture and art have faced new challenges and problems but also they have acquired real perspectives to be developed and led to the universal level. Today a continuing process of national self-identiﬁ cation of Kazakhstan’s art is inﬂ uenced by current global trends on the one hand and on the other one there can be noticed a strong inclination towards ancient traditional forms of artistic expressiveness. The question of philosophical essence, word-view basis and axiological orientation in the independent Kazakhstan’s contemporary art seems to be paramount in the present conditions of formation of an adequately perceived national cultural image.